Kidney allograft recipients, immunosuppression, and coronavirus disease-2019: a report of consecutive cases from a New York City transplant center. Issue 7 (17th July 2020) - Lubetzky, Michelle; Aull, Meredith J; Craig-Schapiro, Rebecca; Lee, John R; Marku-Podvorica, Jehona; Salinas, Thalia; Gingras, Laura; Lee, Jun B; Sultan, Samuel; Kodiyanplakkal, Rosy Priya; Hartono, Choli; Saal, Stuart; et al.
Abstract: Background: Kidney graft recipients receiving immunosuppressive therapy may be at heightened risk for coronavirus disease 2019 (Covid-19) and adverse outcomes. It is therefore important to characterize the clinical course and outcome of Covid-19 in this population and identify safe therapeutic strategies. Methods: We performed a retrospective chart review of 73 adult kidney graft recipients evaluated for Covid-19 from 13 March to 20 April 2020. Primary outcomes included recovery from symptoms, acute kidney injury, graft failure and case fatality rate. Results: Of the 73 patients screened, 54 tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)—39 with moderate to severe symptoms requiring hospital admission and 15 with mild symptoms managed in the ambulatory setting. Hospitalized patients were more likely to be male, of Hispanic ethnicity and to have cardiovascular disease. In the hospitalized group, tacrolimus dosage was reduced in 46% of patients and mycophenolate mofetil (MMF) therapy was stopped in 61% of patients. None of the ambulatory patients had tacrolimus reduction or discontinuation of MMF. Azithromycin or doxycycline was prescribed at a similar rate among hospitalized and ambulatory patients (38% versus 40%). Hydroxychloroquine was prescribed in 79% of hospitalized patients. Graft failure requiring hemodialysis occurred in 3 of 39 hospitalized patients (8%) and 7 patients died, resulting in a case fatality rate of 13% among Covid-19-positive patients and 18% among hospitalized Covid-19-positive patients. Conclusions: Data from our study suggest that a strategy of systematic triage to outpatient or inpatient care, early management of concurrent bacterial infections and judicious adjustment of immunosuppressive drugs rather than cessation is feasible in kidney transplant recipients with Covid-19.